Protocol on medico-legal documentation of threats - Pérez-Sales, Pau; Brasholt, Marie; Podolian, Olena; Honchar, Yulia; Cakal, Ergün; Søndergaard, Elna (Torture Journal, 2023)
Introduction. The use of threats remains prevalent in law enforcement practices in many parts of the world. In studies with torture survivors, credible and immediate threats have been considered a distinctly harmful method of torture. Notwithstanding this prevalence, there is a considerable degree of difficulty in legally substantiating and establishing harms produced by threatening acts. It is also generally difficult to clearly identify the harms that go beyond the fear and stress inherent (therefore not unlawful) in law enforcement practices. We present a Protocol on Medico- Legal Documentation of Threats. The aim of the Protocol is to improve documentation and assessment of harms so that stronger legal claims can be submitted to local and international complaints mechanisms. Methods. The Protocol has been developed based on a methodology initiated by the Public Committee against Torture in Israel (PCATI), REDRESS and the DIGNITY - Danish Institute against Torture (DIGNITY) involving: compilation and review of health and legal knowledge on threats; initial drafting by the lead author; discussion among the members of the International Expert Group on Psychological Torture; pilot-testing in Ukraine by local NGO Forpost; adjustments were made according to the results of the pilot study. Results. We present the final Protocol and a Quick Interviewing Guide. This Protocol is cognisant of the significance of the specific social, cultural, and political contexts in which threats are made and might be subjected to adaptations to specific contexts. We hope that it will improve the documentation of threats as a torture method or as part of a torturing environment, as well as inform efforts on their prevention more broadly.